MORPHOPHYSIOLOGICAL CHANGES IN SEEDLINGS OF Eugenia uniflora L. AFTER CHEMICAL HARDENING - Vera Cruz, Maria Soraia Fortado; Klosowski, Élcio Silvério; Souza, Fernanda Ludmyla Barbosa; Rocha, Maria Eunice Lima; Ristau, Ana Carolina Pinguelli; Malavasi, Ubirajara Contro (Floresta, 2024)
Using quality seedlings increases the chances of survival and development after planting. Hardening aims to modify the morphology of seedlings to acclimatize them to stressful field conditions. The objective of this study was to quantify the effects of chemical hardening with methyl jasmonate on the morphophysiology of Eugenia uniflora L. seedlings subjected to 12 days of water deficit. Seedlings were hardened with doses of 0, 50, 100, and 150 μmol L-1 of methyl jasmonate (MeJA). Afterward, they were transplanted into pots with soil and subjected to water deficit for 12 days. During that period, we assessed shoot height (H), stem diameter (SD), leaf area (LA), leaf dry mass (LDM), stem dry mass (SDM), root dry mass (RDM), total dry mass (TDM), relative water content (RWC), robustness index (RI), Dickson quality index (DQI), shoot/root ratio (S/R), stomatal conductance (Sc) and evapotranspiration (ET). The experiment was conducted in a randomized block design with five blocks. Variables RI, DQI, LA, RWC, and TDM values presented a quadratic trend, with promising results from the 50 and 100 µmol L-1 doses. Sc and ET values were influenced by water deficit. Under conditions of water restriction, application of MeJA in adequate doses promoted morphophysiological changes and induced defense strategies in E. uniflora seedlings. Doses of methyl jasmonate between 50 and 100 µmol L-1 resulted in seedlings with greater tolerance to water deficit for 12 days.